Penanaman Kemandirian Anak Melalui Pembiasaan Ibadah Taharah di KB Melati Indah Ponorogo - Darti, Darti; Nurjan, Syarifan; Irsad Rusdiani, Nurtina (Generasi Emas, 2024)
This study aims to examine the process of fostering independence in early childhood at KB Melati Indah. The main issue addressed is how this institution implements strategies to develop independence in young children, particularly through the habituation of thaharah practices. The research method used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The results of the study indicate that KB Melati Indah has successfully implemented various effective strategies in fostering independence, such as providing real-life examples and involving children in daily activities that require independence. The habituation of thaharah practices is also taught consistently, helping children understand the importance of cleanliness and personal responsibility. Challenges include limited facilities and support from parents, but these can be overcome through a more integrative and participative approach. Overall, this research demonstrates that with the right strategies, educational institutions can help early childhood develop the independence necessary for their readiness in entering the next level of education.